2020
DOI: 10.38021/asbid.742049
|View full text |Cite
|
Sign up to set email alerts
|

Futbol Hakemlerinin Benlik Saygıları ve Algılanan Stres Düzeyleri Arasındaki İlişkinin İncelenmesi (Düzce İli Örneği)

Abstract: Araştırmanın amacı, futbol hakemlerinin benlik saygıları ve algılanan stres düzeyleri arasındaki ilişkinin incelenmesidir. Amaca istinaden, araştırmanın modeli için nicel araştırma türlerinden olan tarama ve korelasyon modeli (Demir, 2015) seçilmiştir. Çalışma grubu; Düzce ilinde faal futbol hakemleri arasından gönüllü katılım sağlayan %19 ile 18-20 yaş, %21,4 ile 21-23 yaş, %9,6 ile 24-26 yaş ve %50 ile 27 yaş ve üzeri toplam 42 erkek hakemden oluşmaktadır. Hakemlerin bazı demografik özelliklerini belirlemek … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…Similarly, in the study conducted by Yanık (2017), it was found that there was no difference between the stress levels of the participants according to their marital status. The results of the studies conducted by Görün et al (2020) and Yanık (2017) were parallel with the results of this study. Similarly, no statistically significant difference was found between the job performance levels of the individuals according to their marital status.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, in the study conducted by Yanık (2017), it was found that there was no difference between the stress levels of the participants according to their marital status. The results of the studies conducted by Görün et al (2020) and Yanık (2017) were parallel with the results of this study. Similarly, no statistically significant difference was found between the job performance levels of the individuals according to their marital status.…”
Section: Discussionsupporting
confidence: 87%
“…In other words, although the perceived stress levels of single individuals were higher than married participants, this difference was not significant. In the study conducted by Görün et al (2020), no significant difference determined between the stress levels perceived by the participants according to their marital status. Similarly, in the study conducted by Yanık (2017), it was found that there was no difference between the stress levels of the participants according to their marital status.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, According to Yurtsever (28), it was reported that there was no statistically significant difference between stress symptoms and the age factor. Görgün et al (12) found that there was no significant difference between the age of the referees and the perceived stress levels in a study they conducted with football referees.…”
Section: Discussionmentioning
confidence: 96%
“…Yapılan tüm etik ve sportmenlik dışı davranışlar hakemlerde gerginlik ve beraberinde stresi getirmektedir. Stres kavramı, kişilerin hayattan aldıkları doyumu azaltan ve hayat ile aralarındaki bağı zayıflatabilen bir duygu durumu olarak ifade edilmektedir (Görün, Öntürk, Engin, Bingöl ve Bayrakdaroğlu, 2020). Stres, bireyler üzerinde etki yapan ve onların davranışlarını, başka insanlarla ilişkilerini etkileyen bir kavramdır.…”
Section: Introductionunclassified